An architecture for making judgments using computing with words - Mendel, Jerry M. (Zielona Góra: Uniwersytet Zielonogórski)
Our thesis is that computing with words needs to account for the uncertainties associated with the meanings of words, and that these uncertainties require using type-2 fuzzy sets. Doing this leads to a proposed architecture for making ?judgments? by means of computing with words, i.e., to a ?perceptual komputer? - the Per-C.
Keywords: computing with words; footprint of uncertainty; perceptual computer; type-2 fuzzy logic system; judgments